KINDERGARTEN TEACHERS’ STRATEGIES TO TEACH ENGLISH VOCABULARY IN A MONOLINGUAL SCHOOL IN AMBARAWA, INDONESIA - Sherly Aggita Putri; Listyani Listyani (Universitas Muria Kudus, 2020)
Living in Ambarawa, which is a small town, an English teacher in such a location has a unique challenge in teaching the target language. This study was conducted at a monolingual kindergarten in Ambarawa, Indonesia. There is one primary question to be answered in this study, which is what strategies were used by English teachers in teaching vocabulary to young learners at a monolingual kindergarten in Ambarawa, Indonesia. Knowing that learning English vocabulary is important, the researchers conducted this research by observing the class ten times and interviewing the English teacher. Class observations, which included the strategies used by the teachers and the learning and teaching process used to collect the data. Besides that, an interview with the teacher was conducted after the class observation to find out the reasons for the teacher in choosing the related teaching strategies. The results of the study presented some various teaching strategies which were used to teach English vocabulary in a monolingual school in Ambarawa. From ten class observations and interviews, three main strategies were identified. The three primary strategies used by the English teacher in a monolingual kindergarten in Ambarawa, Indonesia in teaching English vocabulary to young learners were the use of teaching media, the implementation of appropriate methods and approaches, and the use of fun activities to create a more engaging class. Therefore, given the unique condition of each school, English teachers need to be creative yet wise in choosing the most appropriate teaching strategies to meet the needs of the learners.